Prediction of Lateral Lymph Node Metastasis in Lower Rectal Cancer: Analysis of Paraffin-embedded Sections - Ishida, H.; Hatano, S.; Ishiguro, T.; Kumamoto, K.; Ishibashi, K.; Haga, N. (Japanese journal of clinical oncology, 2012)
In the surgical treatment for lower rectal cancer, preoperative selection of patients at high risk for lateral lymph node metastasis is important, since lateral lymph node dissection might impair genitourinary functions. We examined whether the status of lateral lymph node metastasis can be predicted from the lymph node size. The subjects were 533 (35 positive and 498 negative) lateral lymph nodes from 47 patients with lower rectal cancer who underwent curative resection with lateral lymph node dissection. The sizes of the lateral lymph nodes immediately after removal and those in paraffin-embedded sections were compared for 108 lateral lymph nodes from 13 patients. In addition, receiver-operating characteristic curves were generated for the 533 paraffin-embedded lateral lymph nodes from the 47 patients to determine the optimal cut-off size for discriminating between positive and negative lateral lymph nodes. Irrespective of the presence/absence of metastasis and the long-/short-axis diameter, a positive relationship was noted between the sizes of the lateral lymph nodes measured immediately after removal and those measured on paraffin-embedded sections (P< 0.01). The area under the curve for the short-axis diameter differed little from that for the long-axis diameter (0.77 vs. 0.76, P =0.80). The optimal cut-off values of the short- and long-axis diameter extrapolated to the living body were 5.4 and 8.4 mm, respectively, with an accuracy of 72.8% for the short-axis diameter and 71.9% for the long-axis diameter. Prediction of the status of lateral lymph node metastasis from the lymph node size (long-/short-axis diameter) may be a simple and reliable method. The optimal cut-off diameter should be validated in prospective imaging studies.